2001
DOI: 10.1006/exer.2001.1059
|View full text |Cite
|
Sign up to set email alerts
|

Concentric Retinitis Pigmentosa: Clinicopathologic Correlations

Abstract: Progressive concentric (centripetal) loss of vision is one pattern of visual ®eld loss in retinitis pigmentosa. This study provides the ®rst clinicopathologic correlations for this form of retinitis pigmentosa. A family with autosomal dominant concentric retinitis pigmentosa was examined clinically and with visual function tests. A post-mortem eye of an affected 94 year old family member was processed for histopathology and immunocytochemistry with retinal cell speci®c antibodies. Unrelated simplex/ multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Moreover, we could demonstrate for the first time that this direct contact seems to cause RPE cells to detach from Bruch′s membrane and to migrate along the contacting vessels towards the inner retina. Our murine whole-mount data illustrate the arrangement of pigmented cell clusters outlining retinal capillaries that correlate well with BSPs in humans [3,[8][9][10][11][12]. Moreover, using OCT investigation in an RP patient we could demonstrate perivascular pigmentation in vivo, thereby proving that BSPs are located at different retinal layers ranging from the RPE to the GCL comparable to our findings in the mouse model.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Moreover, we could demonstrate for the first time that this direct contact seems to cause RPE cells to detach from Bruch′s membrane and to migrate along the contacting vessels towards the inner retina. Our murine whole-mount data illustrate the arrangement of pigmented cell clusters outlining retinal capillaries that correlate well with BSPs in humans [3,[8][9][10][11][12]. Moreover, using OCT investigation in an RP patient we could demonstrate perivascular pigmentation in vivo, thereby proving that BSPs are located at different retinal layers ranging from the RPE to the GCL comparable to our findings in the mouse model.…”
Section: Discussionsupporting
confidence: 83%
“…In a number of histological studies on human donor eyes, BSPs were found only in areas devoid of photoreceptors, and were formed by RPE cells migrating along retinal vessels [3,[8][9][10][11][12]. However, the trigger for detachment of RPE cells from Bruch′s membrane and successive migration has still remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations